2015
DOI: 10.4103/2229-516x.162273
|View full text |Cite
|
Sign up to set email alerts
|

Teaching communications skills to medical students: Introducing the fine art of medical practice

Abstract: Introduction:Like many other people based professions, communications skills are essential to medical practice also. Traditional medical teaching in India does not address communication skills which are most essential in dealing with patients. Communication skills can be taught to medical students to increase clinical competence.Objective:To teach basic communication and counseling skills to fourth-year undergraduate students to increase their clinical competence.Methodology:A total of 48, fourth-year MBBS stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
73
0
9

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(87 citation statements)
references
References 10 publications
(19 reference statements)
5
73
0
9
Order By: Relevance
“…[5] Despite this fact, communication skills’ training happens to be an area that is often neglected. [6] It is therefore the need of the hour to invest in resources to enhance the “communication skills bank” of the medical graduates.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[5] Despite this fact, communication skills’ training happens to be an area that is often neglected. [6] It is therefore the need of the hour to invest in resources to enhance the “communication skills bank” of the medical graduates.…”
mentioning
confidence: 99%
“…The evaluation, which was based on a checklist prepared, using the modified Calgary-Cambridge guide, showed a significant improvement in the posttraining scores. In view of these and findings of other studies,[567] the researchers planned the current study to explore the students’ view points of the role-play and also to ascertain if learning communication skills was a felt need by students for their future clinical practice.…”
mentioning
confidence: 99%
“…The present study needs to be more comprehensive to extract such a conclusion. Improvement in knowledge has been assessed using various strategies like OSCE (Objective Structured Clinical Examination), [12,13] SP [13], True False Statements, Multiple and Single Choice Questions. No goal standard assessment model has been suggested as different assessment methods have different values.…”
Section: Discussionmentioning
confidence: 99%
“…12 In another study, it was found that training about communication skills is often lacking and that further endorses the results of this study about need of imparting these skills to the students in their formative years. 13 It has been correctly stated by Manias, "Medication communication is a vital component of patient safety, quality of care, and patient and family engagement''. 14 In this regard, the role play demonstrations to teach them the communication skills were well accepted by the students and they felt that this approach enhanced their ability to explain drug therapy to a patient.…”
Section: Discussionmentioning
confidence: 99%